Hubungan Penggunaan Kontrasepsi Hormonal Suntik Satu Bulan Dan Tiga Bulan Dengan Gangguan Menstruasi Pada Wanita Usia Subur - Linda Juwita; Ninda Ayu Prabasari; Anggi Siska Mega Selvia (JURNAL NERS LENTERA, 2021)
Users of hormonal contraception experience side effects, including menstrual disturbances and changes in body weight. The emergence of these side effects has an impact on the drop in family planning participants. The purpose of this study was to determine the relationship between the use of hormonal contraception for one month and three months with menstrual disorders in women of childbearing age. The research method is descriptive analytic with a cross sectional approach. The independent variable is the use of hormonal contraception for 1 and 3 months, the dependent variable is menstrual disorders. The population in this study were all contraceptive injection acceptors for 1 month and 3 months of use in the independent practice of midwife F Sri Retnaningtyas Surabaya, which operated 120 people. The sampling technique used is purposive sampling. The sample that met the inclusion and exclusion criteria was 65 respondents. The results showed that the majority of respondents were aged 26-35 years, had a high school education, did not work and had 2-3 children. Chi Square Asymp test results. Signature (2-sided) 0.704>0.05, which means that there is no relationship between the use of hormonal contraception for one month and three months with menstrual disorders in women of childbearing age. Side effects experienced by injectable family planning acceptors varied, including nausea, dizziness, headaches, and weight gain.